The cultures of markets: the political economy of climate governance - Knox-Hayes,Janelle (Oxford University Press, 2016)
This book explores the establishment of emissions trading as a form of environmental, market-based governance. It conceptualizes markets as institutions, and analyzes them as a system of climate governance. To this end, it argues that international efforts to promulgate markets run up against local cultures of markets that shape economic practices and knowledge to different degrees. The book also examines the material implications of emissions markets on the environment and climatic systems. In sum, the study finds that cultures of markets present a substantial challenge to a universalist prescription for resolving climate change and highlights issues at the interface of political and economic governance in different political economies. This includes issues of citizen, state, and industry participation, and the materiality of economic and financial productivity.